SMU appoints new Provost and School of Social Sciences Dean - Singapore Management University (Institutional Knowledge at Singapore Management University, 2019)
Singapore Management University (SMU) today officially announced the appointment of its new Provost and Dean for the SMU School of Social Sciences (SOSS). Provost-Designate Professor Timothy Clark will take office from 1 April 2019, while SMU SOSS Dean-Designate Professor Chandran Kukathas will join the University from 1 July 2019.